Facial synthesis of reduced grapheneoxide/magnetite nanocomposite for energy generation and toxic metal bioremediation via microbial fuel cells - Getabalew Shifera Weldegrum; Demise Alebachew Zemedagegnehu; Aknachew Mebreku Demeku; Tekalign TesfayeTadesse; Nigus Maregu Demewoz; Cheru Talbachew Haile; Endashaw Tilahun Gizaw; Tesfalem Atnafu; Beshir A. Hussein; Abire Huluka Fuli (Scientific Reports)
Abstract Microbial fuel cell (MFC) technology is gaining popularity as a viable and sustainable method of energy and power generation, while simultaneously reducing environmental pollution levels. However, MFCs are not economically feasible due to their low energy productivity and the high cost of producing anode materials. In this study, an anode made of an enset corm biosynthetic graphene derivative (E-rGO) was installed in the dual chamber of an MFC. In addition, a composite anode of E-rGO/Fe3O4 was developed to remove Cr (VI) and Pb (II) ions from wastewater while simultaneously generating energy. The synthesized materials were analyzed using UV–Vis, SEM–EDS, XRD, FTIR, RAMA, and TGA spectroscopy to investigate the materials’ optical, morphological, and structural properties, molecular vibrational states, structural defects, and thermal stability. CV and EIS were also utilized to investigate the electrochemical characteristics of the synthesized materials. For Cr (VI), the anodes made using E-rGO, and E-rGO/Fe3O4 NCs had remediation efficiencies of 70.6%, and 79.2%, while for Pb (II), they were 65.1%, and 73.8%. Furthermore, the composite anode (E-rGO/Fe3O4 NCs) delivered a maximum power density of (39.77 mW/m2) and a current density of (1171 mA/m2), higher than E-rGO modified anode electrode power density (8.75 mW/m2) and current density (609 mA/m2), respectively. The final results of the produced anodes revealed that Enset corm biomass is a viable and affordable material for improving MFC anode performance. The outcome of the manufactured anodes suggests that enset corm biomass is a viable and economical material to improve MFC anode efficiency.